(untitled) (Research, Society and Development, 2020)
Dog attacks on humans occur frequently, since the natural instinct of the species has not been lost even over the years and the occurrence of domestication. With the purpose of understanding the dynamics of the aggressions that occurred in the municipalities of Paraíba do Sul, Barra do Piraí and Paracambi - RJ, during the years 2018 to 2019, this study is based on the response of questionnaires applied to victims of attacks by dogs in the municipalities. Among the 87 questionnaires applied, 42 cases of canine aggressions were found, representing 48.27%. The attacks focused on females, aged between 20 and 45 years of age, affecting the upper limbs and being in the morning. The aggressor dogs in general were males and without defined breed. Emphasizing that the assaulted, did not do prophylaxis with the rabies vaccine and did not present fear of dogs after the attack. It is concluded that the majority of the people attacked did not seek clinical care, being an important measure, since dogs are transmitting zoonoses, such as rabies, causing a great impact on the public health of the population.